Diversity and Path Analysis of Chilli (Capsicum spp.) Based on Morphological Traits in Northern Region of Bangladesh - Deen Mohammad Deepo; Aniruddha Sarker; Suraiya Akter; Md. Mazharul Islam; Mahmudul Hasan; Naheed Zeba (Turkish Journal of Agriculture: Food Science and Technology)
Genetic variability, heritability, genetic advance, correlation coefficient analysis, path coefficient analysis and genetic divergence between yield and its contributing traits were estimated using fifteen (15) different chilli genotypes in northern region of Bangladesh. The aim of this study is to screen out suitable parents for next hybridization program. The phenotypic coefficient of variations was found slightly higher than the genotypic coefficient of variations for all characters studied, indicating that the apparent variation is not only genetic but also influenced by the growing environment in the expression of the traits. High genotypic and phenotypic coefficient of variation was observed in length of fruit (27.27% and 27.81%). High heritability coupled with high genetic advance in percent of mean in fruit yield per plant (71.23 and 39.38), number of fruits per plant (71.26 and 31.18), weight of individual fruit (88.52 and 43.80), length of fruit (96.13 and 70.59) and diameter of fruit (79.58 and 35.79) suggested that these characters would be considered for varietal selection. The correlation studies revealed that fruit yield per plant showed significant positive correlation with plant height (0.369), number of fruits per plant (0.587), weight of individual fruit (0.634) and length of fruit (0.450) which can be considered for selection of a good variety. Path analysis revealed weight of individual fruit (0.293), plant height (0.205), number of branches per plant (0.186), length of fruit (0.164), number of fruits per plant (0.132) and diameter of fruit (0.078) had direct positive effect on yield per plant, indicating these traits are the main contributors to fruit yield per plant. The divergence value for cluster analysis showed the highest inter-cluster distance between clusters II and IV which indicates that these genotypes may provide high heterosis in hybridization and expected to show wide variability in genetic architecture.